PENGARUH LITERASI KEUANGAN, PENDAPATAN SERTA MASA BEKERJA TERHADAP PERILAKU KEPUTUSAN INVESTASI - MERTHA DEWI, IGA; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.07.TAHUN 2018DO - 10.24843/EEB.2018.v07.i07.p04, 2018)
Research respondents are employees of PT Bank Pembangunan Daerah Bali Branch Renon with a sample of 76 people. Sampling technique in this research use random sampling. Data were analyzed by using Multiple Linear Regression Analysis. The result of this indicate that financial literacy, income has a positive effect on investment decision behavior, but the work period positively has no effect on investment decision behavior. This is because in the banking industry, the entire new employee and who have been working long time get the training and obtain informations about financial developments and financial conditions that occur at this time. In the other words the undertanding of financial literacy and employee behavior is almost the same. Based on the results of statistical data, financial literacy variables have the most influence in determining the behavior of investment decisions compared to income. This explains that a good understanding of finance is a major factor in determining an invesment decisions.